Asian Conference on Biomedical Research and Laboratory Medicine 2021 - Wan Ahmad, Wan Amir Nizam; Kaderi, Mohd Arifin; Masre, Siti Fathiah; Budin, Siti Balkis; Kuppusamy, Umah Rani; Raja Aziddin, Raja Elina; Sarchio, Seri Narti Edayu; Sukardi, Sabrina; Md Akim, Abdah; Cheah, Yoke Kqueen; Rajab, Nor Fadilah; Taib, Izatus Shima; et al. (Life Sciences, Medicine and Biomedicine, 2022)
Asian Conference on Biomedical Research and Laboratory Medicine was organized by three associations: Malaysian Association of Clinical Biochemists (MACB), Association of Scientific Officers Ministry of Health (ASOMH), and Malaysian Biomedical Science Association (MyBIOMED). The conference was held on 24th-25th August 2021 and a workshop on 26th August 2021 through Webex Webinar Platform with the theme of “Revolutionising laboratory medicine through research and innovation”. This conference aimed to bring together leading academic, scientists, laboratory medical scientists, pathologists, researchers, and research scholars to exchange and share their experiences and research results about all aspects of laboratory medicine and health sciences. There was a total of almost 500 participants registered and over 100 abstracts submitted for this conference.